2016
DOI: 10.3892/mmr.2016.6042
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulated microgravity culture improves the proliferation and odontogenic differentiation of dental pulp stem cell in PLGA scaffolds implanted in mice

Abstract: Tooth regeneration through stem cell-based therapy is a promising treatment for tooth decay and loss. Human dental pulp stem cells (hDPSCs) have been widely identified as the stem cells with the most potential for tooth tissue regeneration. However, the culture of hDPSCs in vitro for tissue engineering is challenging, as cells may proliferate slowly or/and differentiate poorly in vivo. Dynamic three‑dimensional (3D) simulated microgravity (SMG) created using the rotary cell culture system is considered to an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Indeed, previous report show that simulated μ G promotes the proliferation and differentiation of human mesenchymal stem cells [57]. Similar findings were also made in experiments using human dental pulp stem cells [58] and human epidermal stem cells [59], including the result of an increased percentage of Ki67-positive cells. These reports support our finding that C-ion irradiation and simulated μ G together promote cell cycle progression.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, previous report show that simulated μ G promotes the proliferation and differentiation of human mesenchymal stem cells [57]. Similar findings were also made in experiments using human dental pulp stem cells [58] and human epidermal stem cells [59], including the result of an increased percentage of Ki67-positive cells. These reports support our finding that C-ion irradiation and simulated μ G together promote cell cycle progression.…”
Section: Discussionsupporting
confidence: 80%
“…Dynamic three‐dimensional (3D) simulated microgravity (SMG) created using the rotary cell culture system is considered to an effective tool, which contributes to several cell functions. A recent study by Li et al () has used various histological and immunohistochemical examinations of Ki‐67, dentin sialoprotein, type I collagen and DMP‐1, and found that both the proliferation and odontogenic differentiation abilities of the hDPSCs that were prepared in the 3D SMG culture system were higher, compared with those prepared in the static culture system. These results suggested that dynamic 3D SMG abilities of hDPSCs in vivo (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, several studies have proven that dental MSCs can induce the regeneration of not only dental tissues including enamel, dentin, tooth pulp, and PDL but also other organs that share the same developmental origins such as bone and salivary gland [65,111]. Cell modification approaches such as cell immortalization, hypoxic culture condition, and 3-dimensional spheroid formation have been applied to potentiate the stemness and differentiation capacity [111][112][113]. It is further noted that native and synthetic biomaterials can be combined with dental MSCs to provide a physical scaffold that supports engraftment and differentiation of transplanted cells.…”
Section: Tissue Regenerationmentioning
confidence: 99%